The (im)possibility of communication - Bert Olivier (Communicare)
This paper addresses the question of communication from a perspective opened up by Derrida’s reading of Joyce’s Ulysses in terms of the relationship between the notion of the ‘yes’ or iterability, the signature of (and counter-signature to) a text and two types of laughter. It is shown that the same aporia that confronts the reader of Ulysses, namely that a counter-signature to the text is possible as a novel event and is simultaneously not possible as such, faces participants in communication: communication is and is not possible. The work of Hardt and Negri is further used to add another dimension to this aporia, this time focusing on the paradox of living in a so-called ‘age of communication’, while certain events of resistance to the agencies of global hegemony are incommunicable.